The Effect of Training Using Hand Paddles and Fins on Craw Swimming Speed ​​at the SPC Swimming Club: The Effect of Training Using Hand Paddles and Fins on Craw Swimming Speed ​​at the SPC Swimming Club - Dwingki, Dwingki Marta Putra; Megi Personi; Dody Ertanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to determine the effect of training using hand paddles and fins on the crawl swimming speed of athletes from the ULMA Swimming Club. The study was conducted over a period of approximately two months at the Tanah Pata Swimming Pool in Bengkulu City, with a total of 16 training sessions. The research method used was an experiment, with a sample of 20 male athletes selected through purposive sampling, specifically athletes from age groups 4 and 5. The instrument used was a crawl stroke (freestyle) swimming speed test. Data analysis was conducted through analysis prerequisite tests, including normality tests, homogeneity tests, and hypothesis tests. The normality test results showed that the pretest and posttest data had a normal distribution, with Lhitung < Ltabel (0.112 < 0.190 for the pretest and 0.165 < 0.190 for the posttest). The homogeneity test showed that the data was homogeneous, with Fhitung = 0.78 < Ftabel = 3.52. From the data analysis, the correlation coefficient was found to be r = 0.93 and the determination coefficient was 85.63%, indicating that training using hand paddles and fins has a very strong influence on improving crawl swimming speed. Therefore, it can be concluded that this training program is effective in enhancing crawl swimming performance in young athletes.